Method for Surgical Treatment of Hammer Deformity of the Second Toe - S. N. Leonova; I. V. Usoltsev; M. A. Kosareva (Acta Biomedica Scientifica)
The article presents a case of successful surgical treatment of a patient with hammer-like deformity of the second toe associated with deformity of the first toe. During the preoperative examination of the patient, the length of the required shortening of the second metatarsal bone relative to the length of the third metatarsal bone was calculated on the X-ray in frontal projection and the length of the required shortening of the first metatarsal bone was calculated using a known method. To eliminate the deformity of the first toe, the author’s method of surgical treatment was used. To correct the deformation of the second toe, the proposed method was used, which includes the following steps: marking the lines of osteotomies during the operation; performing osteotomies along the outlined lines; removal of a free bone fragment; precise implementation of  the required shortening of the second metatarsal bone; fixation of the osteotomized fragments of the second metatarsal bone with a cannulated screw. As a result of the performed surgical treatment, correction of the hallux valgus and hammer-like deformity of the second toe was achieved.The presented clinical case shows that in the surgical treatment of hammer deformity of the second toe, it is important to take into account the individual characteristics of the patient’s foot condition, namely, the ratio of the length of the second and adjacent third metatarsal bones. Preliminary calculation of the length of the required shortening of the second and first metatarsal bones on the roentgenogram, precise markings of the  osteotomy lines and the implementation of the necessary shortening contribute to achieving a balance in the ratio of the lengths of the metatarsal bones, restoring the optimal load distribution on the heads of the metatarsal bones, more accurate correction of the deformity of the second and first toes, and improving statodynamic function of the foot and reducing the risk of postoperative failures.